Population Structure and Dynamics of Beef Cattle in Sidenreng Rappang Regency, South Sulawesi, Indonesia - Sardi, Rezky Yuniar; Nugraha, Angga; Mansur, Musdalifa (Hasanuddin Journal of Animal Science (HAJAS), 2024)
This study aimed to analyze the population structure and dynamics of beef cattle in Bulo Timoreng Village, Panca Rijang District, Sidenreng Rappang Regency, South Sulawesi, Indonesia. The research was conducted from March to April 2023 using a survey method with 53 respondents selected purposively. Data were collected through observation and interviews, then analyzed descriptively to determine population structure and population dynamics based on the percentages of births, deaths, and slaughter of productive females. The population structure consisted of 60.47% cattle (21.34% males and 39.13% females), 28.26% heifers (15.47% males and 12.79% females), and 11.27% calves (5.72% males and 5.55% females). The birth rate was 11.27%, mortality rate 3.62%, and the slaughter rate of productive females 1.65%. The findings are highly relevant for formulating livestock development strategies and increasing cattle population growth in South Sulawesi. This study provides novel insights into how local population data can guide sustainable livestock policies, serving as a regional model for achieving the Sustainable Development Goals (SDGs), particularly Goal 2: Zero Hunger. Keywords: Beef cattle, population dynamics, South Sulawesi, livestock policy, sustainable development